An assessment of serum 57Co cyanocobalamin as an index of vitamin B12 absorption1. Issue 7 (October 1970) - Donaldson, D.; Blight, B. J. N.; Lascelles, P. T.
Abstract : A technique has been developed for accurately assaying serum and urine 57 Co cyanocobalamin during the conventional Schilling test. Serum and urine radioactivity in a large number of patients has been correlated and the precise normal limits have been determined by statistical analysis. The implications of this for investigating conditions other than pernicious anaemia and the malabsorption syndromes are stressed.